Long-Lived Quantum Coherence in the Fenna-Matthews-Olson Complex: Implications for Energy Transfer Efficiency in Photosynthesis - Chai Pao; Rit Som; Daiki Nishida (Journal of Tecnologia Quantica, 2025)
Quantum coherence has been shown to play a crucial role in optimizing energy transfer in photosynthetic systems, especially in the Fenna-Matthews-Olson (FMO) complex, which is responsible for efficiently capturing light energy in photosynthetic bacteria. While quantum coherence is often considered fragile and short-lived in biological systems, recent studies have indicated its potential for sustaining long-lived coherence, facilitating highly efficient energy transfer. This research investigates the implications of long-lived quantum coherence in the FMO complex for energy transfer efficiency, exploring how coherence persistence enhances the system’s performance. The objective of this study is to analyze the effects of long-lived quantum coherence on energy transfer efficiency in the FMO complex under varying environmental conditions, such as temperature and bath coupling. The results demonstrate that long-lived quantum coherence directly correlates with higher energy transfer efficiency, with temperature and environmental factors playing a significant role in maintaining coherence. The study shows that the FMO complex utilizes quantum coherence as an active resource to optimize energy conversion, achieving efficiencies well beyond classical expectations. In conclusion, this research underscores the importance of quantum coherence in biological energy transfer processes and offers insights into bio-inspired quantum systems for efficient energy harvesting.